1978
DOI: 10.1136/bmj.2.6150.1460
|View full text |Cite
|
Sign up to set email alerts
|

Fluid loading to reduce abnormalities of fetal heart rate and maternal hypotension during epidural analgesia in labour.

Abstract: Summary and conclusionsFetal heart rate (FHR) was recorded and maternal blood pressure measured in 104 patients in whom lumbar epidural analgesia was induced in labour. Fifty-one patients received an intravenous load of 1 1 of Hartmann's solution immediately before the epidural injection. This infusion significantly reduced the incidence of abnormalities of FHR from 34% to 12% and of maternal hypotension from 28% to 2%.We did not study mothers with pre-eclampsia and hypertension, but we conclude that there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…20-23 Prophylactic intravenous volume and/or vasopressor administration is commonly used prior to regional anesthesia to minimize the occurrence of hypotension. 16,22,24 In our previously published studies, we have observed that Class III obese women (Body Mass Index, BMI ≥40 kg/m 2 ) undergoing regional anesthesia for childbirth have more anesthesia-related hypotension and fetal heart rate abnormalities than lean gravidas. 25,26 These factors may contribute to the increased cesarean delivery rate and associated perioperative morbidity among Class III obese women, such as hemorrhage, endometritis, wound infection, venous thromboembolism, and respiratory depression.…”
Section: Introductionmentioning
confidence: 97%
“…20-23 Prophylactic intravenous volume and/or vasopressor administration is commonly used prior to regional anesthesia to minimize the occurrence of hypotension. 16,22,24 In our previously published studies, we have observed that Class III obese women (Body Mass Index, BMI ≥40 kg/m 2 ) undergoing regional anesthesia for childbirth have more anesthesia-related hypotension and fetal heart rate abnormalities than lean gravidas. 25,26 These factors may contribute to the increased cesarean delivery rate and associated perioperative morbidity among Class III obese women, such as hemorrhage, endometritis, wound infection, venous thromboembolism, and respiratory depression.…”
Section: Introductionmentioning
confidence: 97%
“…Collins et al in 1978, showed that fluid preloading significantly reduces abnormalities in fetal heart rate (FHR) (34% to 12%) and maternal hypotension (28% to 2%) during epidural analgesia. 63 They excluded patients with preeclampsia and pre-existing hypertension. However, Collins original study used bupivacaine 0.375%, a concentration that is not commonly used in current practice, and probably the cause for significant hypotension.…”
Section: Fluid Preloadingmentioning
confidence: 99%
“…2,5 Decreased fetal cerebral oxygenation, measured with Maternal epidural analgesia in labor may be associated with nonreassuring fetal heart rate (FHR) patterns. This has variously been attributed to epidural agent-induced maternal hypotension resulting in reduced uterine blood flow, 1,2 which may be minimized or avoided by intravenous preload 1,3 ; or near-infrared spectroscopy, has been demonstrated with the mother supine. 11 When FHR changes do occur following administration of epidural analgesia, they may not require expedited delivery for nonreassuring fetal status, 4,6 as the fetus may recover with simple measures such as maternal position change, or discontinuation of oxytocin.…”
mentioning
confidence: 99%